2021
DOI: 10.15252/embj.2020106048
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils induce paracrine telomere dysfunction and senescence in ROS‐dependent manner

Abstract: Cellular senescence is characterized by an irreversible cell cycle arrest as well as a pro-inflammatory phenotype, thought to contribute to aging and age-related diseases. Neutrophils have essential roles in inflammatory responses; however, in certain contexts their abundance is associated with a number of age-related diseases, including liver disease. The relationship between neutrophils and cellular senescence is not well understood. Here, we show that telomeres in non-immune cells are highly susceptible to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
110
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(114 citation statements)
references
References 62 publications
4
110
0
Order By: Relevance
“…However, infection is capable to trigger accelerated TL attrition in telomerase-deficient mice [ 49 ], revealing the existence of telomerase-independent mechanisms linking inflammation to TL shortening. These mechanisms might include the production of ROS during inflammation; for example, via secretion by immune cells such as neutrophils [ 50 ]. Indeed, the rate of telomere shortening increases under oxidative stress, and the G-richness of telomeric DNA renders it highly susceptible to oxidization, leading to the accumulation of 8-oxo-guanine.…”
Section: Telomere Response To Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…However, infection is capable to trigger accelerated TL attrition in telomerase-deficient mice [ 49 ], revealing the existence of telomerase-independent mechanisms linking inflammation to TL shortening. These mechanisms might include the production of ROS during inflammation; for example, via secretion by immune cells such as neutrophils [ 50 ]. Indeed, the rate of telomere shortening increases under oxidative stress, and the G-richness of telomeric DNA renders it highly susceptible to oxidization, leading to the accumulation of 8-oxo-guanine.…”
Section: Telomere Response To Stressmentioning
confidence: 99%
“…Some antioxidant proteins are associated with telomeres (PRDX1 and MTH1) [ 169 , 170 ]. Recently, it was shown that the ROS secreted by activated neutrophils leads to teloxidation of neighboring cells and senescence [ 50 ]. Besides, extra telomeric functions of the telomerase subunits TERT and TERC have been related to modulating mitochondrial metabolism.…”
Section: The Telomere Hormesis Hypothesismentioning
confidence: 99%
“…We observed that many of the genomic regions which had the highest increases in ⍰H2AX and H4K16ac in steatosis, also had relatively high levels (compared to the rest of the genome) in cells grown in control media. This suggests that these regions, such as the telomere-proximal cluster which contains TERT , may be predisposed for sensitivity 33 . There is an abundance of recent literature on the role of epigenetic modifications altering the expression of TERT in cancer via transcriptional and post-transcriptional mechanisms 34 , but the potential for the epigenetic states promoting mutagenesis has been hypothetical 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Recruited neutrophils promote the activation of fibroblasts and contribute to the turnover of the extracellular matrix in both normal and pathologic wound healing [ 18 ]. Furthermore, IL-8 is consistently observed in SASP [ 19 ] and paracrine signaling by neutrophils has been demonstrated to cause cellular senescence [ 20 , 21 ]. However, the specific role of cellular senescence in MWCNT induced fibrotic responses is poorly understood.…”
Section: Introductionmentioning
confidence: 99%